2021
DOI: 10.1073/pnas.2108790118
|View full text |Cite
|
Sign up to set email alerts
|

The binding of the small heat-shock protein αB-crystallin to fibrils of α-synuclein is driven by entropic forces

Abstract: Molecular chaperones are key components of the cellular proteostasis network whose role includes the suppression of the formation and proliferation of pathogenic aggregates associated with neurodegenerative diseases. The molecular principles that allow chaperones to recognize misfolded and aggregated proteins remain, however, incompletely understood. To address this challenge, here we probe the thermodynamics and kinetics of the interactions between chaperones and protein aggregates under native solution condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
6
14
0
Order By: Relevance
“…On the c ( s ) distribution for HspB5 + Ph b under given conditions, the peak (20.4 S) corresponding to free αB-Cr disappears, and peaks with lower sedimentation coefficients appear, corresponding to smaller oligomeric complexes of chaperone-Ph b . This is consistent with the findings of Schiedt et al [ 7 ]. Based on the thermodynamic and kinetic characteristics of the binding of αB-Cr to α-synuclein fibrils, the authors concluded that there was a step of chaperone activation through the disassembly of chaperone complexes [ 7 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…On the c ( s ) distribution for HspB5 + Ph b under given conditions, the peak (20.4 S) corresponding to free αB-Cr disappears, and peaks with lower sedimentation coefficients appear, corresponding to smaller oligomeric complexes of chaperone-Ph b . This is consistent with the findings of Schiedt et al [ 7 ]. Based on the thermodynamic and kinetic characteristics of the binding of αB-Cr to α-synuclein fibrils, the authors concluded that there was a step of chaperone activation through the disassembly of chaperone complexes [ 7 ].…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with the findings of Schiedt et al [ 7 ]. Based on the thermodynamic and kinetic characteristics of the binding of αB-Cr to α-synuclein fibrils, the authors concluded that there was a step of chaperone activation through the disassembly of chaperone complexes [ 7 ]. This mechanism is consistent with previous findings on substrate activation and disassembly of other sHsps with anti-aggregation activity [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…75 One example of how this issue is sidestepped is by using intrinsically-disordered regions, either through coupled folding and binding, 77,78 or through a disordered region far from the binding site affected allosterically. 79 Other routes to decoupling specificity and affinity relate to the entropy of the ligand, oligomeric complex, 80 or solvent. 81,82…”
Section: Discussionmentioning
confidence: 99%